2014
DOI: 10.1021/am404965p
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Cycling Performance of LiNi0.6Co0.2Mn0.2O2 Cathode Active Materials by a Dual-Conductive Polymer Coating

Abstract: LiNi0.6Co0.2Mn0.2O2 cathode materials were surface-modified by coating with a dual conductive poly(3,4-ethylenedioxythiophene)-co-poly(ethylene glycol) (PEDOT-co-PEG) copolymer, and their resulting electrochemical properties were investigated. The surface-modified LiNi0.6Co0.2Mn0.2O2 cathode material exhibited a high discharge capacity and good high rate performance due to enhanced transport of Li(+) ions as well as electrons. The presence of a protective conducting polymer layer formed on the cathode also sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(118 citation statements)
references
References 47 publications
3
115
0
Order By: Relevance
“…The SAED pattern corresponding to the PP-coated layer (right side) exhibited a hollow ring pattern without bright spots, thus indicating that the coated layer consisted of disordered polymer materials. The image in the right inset shows some bright spots in the SAED pattern, which is typical of crystalline NCS cathode material [2,8]. These results thus provide conclusive evidence that the NCS particles are uniformly coated by the nano-sized polymer layer.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The SAED pattern corresponding to the PP-coated layer (right side) exhibited a hollow ring pattern without bright spots, thus indicating that the coated layer consisted of disordered polymer materials. The image in the right inset shows some bright spots in the SAED pattern, which is typical of crystalline NCS cathode material [2,8]. These results thus provide conclusive evidence that the NCS particles are uniformly coated by the nano-sized polymer layer.…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, the conductive polymer coating layer effectively suppresses the SEI film formation and HF attack by blocking the contact between the electrolyte and the cathode material. A simple coating methods has been reported by D.W. Kim and coworkers [8]. However, it is difficult to apply to the cathode material because of the high price of conductive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The cells containing 0.5_E_VC_TTSPi or 0.5_EE_VC_TTSPi electrolyte experienced rapid capacity fade at both testing temperatures. Nelson et al 25 Ma et al 24 and others [43][44][45] have shown that the major reason for rapid capacity loss in NMC/graphite cells tested at 55…”
Section: Resultsmentioning
confidence: 98%
“…To solve these defects, some conductive polymers and fast ionic conductor materials were widely used as surface coating layer on the cathode active materials. [24][25][26][27][28][29][30] materials is coated with various amount of LBO glass via a simple wet chemical process followed by heat-treatment. As expected, the LBO coated materials exhibit obvious improvement both in electrochemical performances and thermal stability under high voltage.…”
Section: Introductionmentioning
confidence: 99%